STUDI ANALISIS DAN SIMULASI PENINGKATAN PRODUKTIVITAS EXCAVATOR HITACHI EX1900-6 DALAM PENGUPASAN OVERBURDEN PADA TAMBANG BATUBARA PT. MANDALA KARYA PRIMA JOBSITE PT. MANDIRI INTIPERKASA PROVINSI KALIMANTAN UTARA - Amrina Aulia Siregar; Sumarya Sumarya (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. PT. Mandala Karya Prima is a mining contractor trusted by PT. Mandiri Intiperkasa for coal mining activities. In the overburden dismantling process, PT. Mandala Karya Prima uses the Hitachi EX-1900-6 excavator with a 12 m3 bucket capacity. This research was motivated by the planned overburden dismantling activity using Hitachi EX1900-6 excavators of 600 bcm / hour not reaching the target. The actual productivity of Hitachi EX1900-6 excavators for wet clay material is 556.8 lcm / hour and for sandstone material is 548.9 lcm / hour.Components that influence the productivity of excavators include material types, front loading conditions, loading methods, and skill operators. These components make work efficiency, bucket fill factor and cycle time not optimal. The actual time cycle when collecting data in the field is 38.63 seconds for clay wet material and 31.64 for sandstone material. By taking the example of cycle time, the clay wet material is 38.63 seconds, the digging rate should be 812.78 lcm / hour. But the reality in the field, the productivity of overburden dismantling of wet clay material is 556.8 lcm / hour. This loss of productivity occurs due to obstacles namely moving the front, repairing fronts, waiting hauler, spotting time, preparing position, and operator needs. Of these obstacles, the biggest contributor to loss of productivity is the waiting hauler which is ± 150 lcm / hour.Based on the theoretical formula of excavator productivity, factors that can be improved to optimize excavator productivity are work efficiency, bucket fill factor and cycle time. Efforts were made to improve work efficiency, namely dumptruck optimization, equipment management, changing loading patterns, and spotting dumptruck without maneuvering. Efforts are made to reduce cycle time, namely changing the digging pattern and making the optimum bench height. While the effort made to increase bucket fill factor is applying the right excavation technique.Keywords:  Productivity, Excavator, Cycle Time, Bucket Fill Factor,  Job Efficiency.